Gender has no influence on mortality after burn injuries: A 20-year single center study with 839 patients. Issue 1 (February 2019) - Ederer, Ines A.; Hacker, Stefan; Sternat, Nikolaus; Waldmann, Anna; Salameh, Olivia; Radtke, Christine; Pauzenberger, Reinhard
Highlights: The higher risk among women was apparent only in univariate regression analysis. Gender-specific differences diminished after adjusting for confounding factors. Age, %TBSA, inhalation injury, full-thickness burn were predictors of mortality. To conclude, women and men had the same risk of death in our study cohort. Abstract: Background: According to the ABSI – Abbreviated Burn Severity Index – women exhibit an increased risk of succumbing to burn injuries. In contrast, following non-thermal trauma, increased mortality has been shown for the male gender. Therefore, the purpose of this study was to evaluate gender-specific differences among burn patients with special regard to burn mortality. Methods: We retrospectively studied 839 patients who were admitted to the Burn Intensive Care Unit (BICU) and underwent surgical treatment between June 1994 and December 2014. In-hospital mortality was the main clinical endpoint. Odds ratios (ORs) were calculated using univariate and multivariate logistic regression models for the association between sex and mortality. Results: In total, we included 530 male and 309 female burn patients. All patients had at least partial-thickness burns and underwent one or more operative procedures. Women were significantly older than men (mean 60.0 years vs 46.2 years; p < 0.001 ). Despite having smaller injuries (24.6% vs 30.3% total body surface area (TBSA); p < 0.001 ), burn mortality among women significantly differed from that of men (27.8% vs 21.7%; OR 1.39, p = 0.045, 95% CI 1.01–1.92). This association, however, did not persist after adjusting for age, %TBSA, inhalation injury and full-thickness burns (OR 1.07, p = 0.77, 95% CI 0.68–1.70). Conclusions: Despite increasing research directed at women's health, the assoziation between gender and burn mortality has yielded conflicting results. This study does not support a gender-specific difference in burn mortality in our study population.